Mixed Adenoneuroendocrine Carcinoma: Is It a Collision Tumor or a Dedifferentiated Carcinoma?. (11th September 2019) - Nazir, Bushra; Ross, Howard; Mittal, Juhi; Taraif, Suad
Abstract: Mixed adenoneuroendocrine carcinoma (MANEC) of the gastrointestinal tract is uncommon with about 100 cases reported involving esophagus, stomach, colon, rectum, and biliary tree. The aggressive behavior of these tumors is usually dictated by the high-grade neuroendocrine carcinoma (NEC) component, which raises the possibility that these may represent areas of dedifferentiation. We here report an 88-year-old male presenting with rectal bleeding. Colonoscopy identified a fungating, villous, and partially circumferential cecal mass. Biopsy revealed tubular adenoma with focal high-grade dysplasia. However, excision was recommended given the impression of a mass. A right hemicolectomy revealed an 8.7-cm friable and ulcerated mass in the cecum. Initially, eight sections (one per cm) of the tumor were examined and revealed intramucosal adenocarcinoma. However, one of the lymph nodes was replaced by a high-grade poorly differentiated tumor, immunophenotypically consistent with NEC. In search for a primary, the rest of the mass was submitted and subsequent histologic examination revealed areas of transition from villous adenoma to intramucosal and muscle invasive adenocarcinoma in addition to deeply invasive NEC showing marked cytological atypia, brisk mitotic activity (Ki-67 >90%), and lymphovascular invasion. Three lymph nodes had metastatic adenocarcinoma and NEC along with several tumor deposits. Following an uneventful postoperative course, the patient received adjuvant chemotherapy. Our case recapitulates the classic description of MANEC where NEC is usually associated with a differentiated adenocarcinoma, commonly arising from an adenoma. The currently proposed pathogenesis is a collision tumor (previously known as mixed exocrine/endocrine carcinomas). However, we propose viewing MANEC as one tumor rather than two colliding tumors utilizing the concept of dedifferentiation, which has been extensively studied in the GYN literature. In a prior study, we found neuroendocrine expression in 41% of undifferentiated endometrial carcinomas. We therefore propose revisiting larger case series of MANEC with this concept in mind.